PPR IMPLEMENTATION IN MICRO TEACHING COURSE TO IMPROVE STUDENTS’ CONFIDENCE AND COMPASSION - Pratini, Haniek Sri (International Journal of Indonesian Education and Teaching (IJIET), 2017)
This research aims to describe the implementation of Paradigm of Reflective Pedagogy (PPR) in Micro Teaching course by providing experiences to students to facilitate learning with more compassion and careful time management for effective learning. By implementing PPR in Micro Teaching course, students are expected to have Competence (the ability to perform basic teaching skills),  Conscience (confidence in performing the basic teaching skills), and Compassion (concern to the students’ responses in the learning process). The implementation results showed that out of 22 students, as many as 16 students (72.73%) got A’s and 6 students (27.27%) got B’s. The average score on Competence aspect was 82, 89 on Conscience aspect and 84 on Compassion aspect.DOI: https://doi.org/10.24071/ijiet.2017.010201